Oil and Currency Shocks, Financial Efficiency, and Firm Value: Evidence from Emerging Transportation Logistics Markets - Azaluddin, Azaluddin; Hanifa, Lia; Mahmuda, Dewi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines how macroeconomic volatility—captured by oil price and exchange rate shocks—shapes firm value and financial performance in the logistics sector of an emerging market. Using data from 2018–2023 and partial least squares structural equation modeling (PLS-SEM), the analysis reveals that oil price movements significantly enhance both return on equity (ROE) and firm value, while exchange rate fluctuations, when interacting with oil price changes, exert a negative moderating effect on firm value. The results indicate that macro shocks not only influence profitability but also condition the transmission of financial performance into market valuation. The model explains 22.8% of firm value variation and 10.8% of ROE, underscoring the importance of macro-financial integration in valuation models. This study extends firm valuation theory by demonstrating that energy and currency risks are non-neutral to investors in capital-intensive sectors, offering implications for corporate hedging, capital structure design, and investment timing strategies.